Characterizing and TRAPing a Social Stress-Activated Neuronal Ensemble in the Ventral Tegmental Area - Koutlas, Ioannis; Linders, Louisa E.; van der Starre, Stef E.; Wolterink-Donselaar, Inge G.; Adan, Roger A. H.; Meye, Frank J. (Frontiers in Behavioral Neuroscience, 2022)
Social stress is a major contributor to neuropsychiatric issues such as depression, substance abuse and eating disorders. The ventral tegmental area (VTA) is involved in the effects of stress on cognitive and emotional processes perturbed in these disorders. However, the VTA is a cellularly heterogeneous brain area and it remains unclear which of its neuronal populations make up the social stress-sensitive ensemble. The current study characterizes the molecular, topographical and functional properties of VTA social stress-activated cells. First, we used immunohistochemical analysis of Fos protein, a marker of recent increased neuronal activity, to show that acute social stress activates a mainly neuronal ensemble in the VTA (VTASocial stress neurons). Topographical analysis showed that this ensemble, which comprises ~11% of all VTA neurons, occurs across VTA subregions. Further analysis showed that approximately half of the VTASocial Stress neurons express the dopamine synthesis rate-limiting enzyme tyrosine hydroxylase (TH). In a minority of cases this occurred with coexpression of vesicular glutamate transporter 2 (Vglut2). Also part of the ensemble were VTA cells expressing just Vglut2 without TH, and cells expressing the vesicular GABA transporter (VGAT) without TH. Next, using targeted recombination in active populations (TRAP2), we showed that VTASocial stress¬ neurons can be permanently tagged and made tractable for future functional investigations. Using a combination of TRAP2 and patch-clamp electrophysiology we demonstrate that VTASocial Stress neurons exhibit higher excitability than their non-trapped neighbor cells. Overall, this study shows that acute social stress activates an ensemble of neurons throughout the VTA, comprising distinct molecular identities, and with specific electrophysiological features. It also identifies TRAP2 as a tool to make this ensemble tractable for future functional studies.